Current priorities of economy: Lithuania-Ukraine - Gutkevych, Svitlana; Sheremet, Oleg; Jureniene, V.; Jurene, S. (My University, 2020)
Ukraine and Lithuania are countries with different government, economic development which is determined by its specializations, population and area, GDP per capita. Economic potential of these countries is aimed at improvement of the population living standards. Lithuania is a member of European Union and it represents the creative industries including tourism. Ukraine is integrating into European Union; it is a country with great potential of food security and tourism as well. Україна і Литва – країни з різним державним устроєм, економічний розвиток яких визначається їх спеціалізаціями, населенням і площею, ВВП на душу населення. Економічний потенціал цих країн спрямований на підвищення рівня життя населення. Литва є членом Європейського Союзу і представляє креативні індустрії, включаючи туризм. Україна інтегрується в Європейський Союз; це країна з великим потенціалом продовольчої безпеки та туризму.
Keywords: кафедра міжнародної економіки; розвиток; харчова промисловість; креативні індустрії; туристична галузь; Creative Industries; food industry; кафедра економіки праці та менеджменту